Patient-doctor communication: Use of complementary and alternative medicine by adult patients with cancer - Oh, B.; Butow, P.; Mullan, Barbara; Clarke, S.; Tattersall, M.; Boyer, M.; Beale, P.; Vardy, J.; Pavlakis, N.; Larke, L. (Society for Integrative Oncology, 2010)
The purpose of this survey was to examine patient–doctor communication about the use of complementary and alternative medicine (CAM) by adult patients with cancer and compare patients' satisfaction with the consultation between patients who had and those who had not discussed the use of CAM with their doctors. Oncologists from three hospitals screened patients for eligibility. Eligible patients were mailed a letter of invitation with a questionnaire (N = 1,323). Three hundred eighty-one questionnaires were returned. Sixty-five percent of cancer patients used at least one form of CAM. Use of CAM was not discussed with the oncologist by 55% of respondents using biologically based CAM and by 80% of those using non–biologically based CAM since the diagnosis of cancer. Patients who discussed the use of biologic CAM with their oncologists were more satisfied with the consultation than those who had not (p = .027), whereas there were no significant differences between patients who discussed or did not discuss use of non–biologically based CAM (p = .102). A substantial proportion of cancer patients do not discuss the use of CAM with their oncologists. It is important to improve patient–doctor communication about the use of CAM to increase patients' satisfaction with the oncology consultation.